Analysis and Evaluation of Performance Parameters of Modified Single Ended Primary Inductance Converter - Hemalatha J N; Hariprasad S A; Anitha G S (Institute of Advanced Engineering and Science, 2017)
The objective of this paper is to propose a modified Single Ended Primary Inductance converter topology with passive lossless snubber cell to achieve Zero Voltage Switching (ZVS) of the device near turn off and Zero Current Switching (ZCS) near turn on. By using the snubber cell effectively with the converter reduces the switching stress by restricting the large variations in voltage and current. The detailed analysis of the circuit with relevant waveforms of the circuit is described. The circuit is designed for a load of 100W at 12V output from an input source ranging between 20-30V. The circuit is modelled in MATLAB Simulink platform and the parameters are compared with conventional circuit. From the results it is shown that the proposed circuit operates at a lesser voltage stress and at higher efficiency than conventional one.